1993
DOI: 10.1111/j.1476-5381.1993.tb13712.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective inactivation of muscarinic M2 and M3 receptors in guinea‐pig ileum and atria in vitro

Abstract: 1 The role of muscarinic M2 and M3 receptors in ileal smooth muscle has been evaluated by use of selective receptor alkylation. The alkylating agents, 4-diphenylacetoxy-N-(2-chloroethyl)-piperidine (4-DAMP mustard) was studied for effects against (+ )-cis-dioxolane, at muscarinic M2 and M3 receptors in guinea-pig atria or ileum, respectively. 4-DAMP mustard (10 nM, 40 min exposure) did not discriminate between these muscarinic receptors. In ileum, 4-DAMP mustard, at 100 nM, resulted in a large dextral shift (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Although no direct contractile response to M2 receptor activation can be demonstrated in guinea-pig ileum (Eglen & Harris, 1993), an indirect influence on contraction via inhibition of P-adrenoceptor-mediated relaxation remains possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no direct contractile response to M2 receptor activation can be demonstrated in guinea-pig ileum (Eglen & Harris, 1993), an indirect influence on contraction via inhibition of P-adrenoceptor-mediated relaxation remains possible.…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of M2 heterogeneous populations of muscarinic receptors (see Eglen receptors by either selective alkylation (Eglen & Harris, 1993) et al, 1994 for a review). Radioligand binding studies have or by treatment with pertussis toxin, which inactivates the demonstrated that the majority of guinea-pig ileal muscarinic guanine nucleotide regulatory protein Gi (Eglen et al, 1988), receptors are of the M2 subtype (-70%), while a minority has minimal effects on guinea-pig ileal contractile responses are of the M3 subtype (-30%), with no measurable quanto muscarinic agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Studies 11,44,[53][54][55] have revealed that > 1 mAChR subtype may be responsible for mediation of cholinergic contraction in tissues. Analysis of results of the study reported here indicated that the effect of bethanechol in the intestinal segments of interest was mediated by both M 2 and M 3 mAChRs, with activation of M 3 mAChRs causing stronger increases in contractility traits than for activation of M 2 mAChRs, as indicated by use of both sets of receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] The fact that this concentration of atropine almost completely abolished the effects of bethanechol confirmed that the mAChRs were blocked and corroborated that the effect of bethanechol is mediated via mAChRs. Concentrations of specific mAChR antagonists used in the study were determined from antagonist affinity values reported in other studies, 8,15,[44][45][46] which allowed maximal occupancy of the receptor subtype of interest with minimal occupation of other subtypes. The mAChR antagonists used in the study reported here possess differing selectivity for the various mAChR subtypes, depending on their affinity patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation